To The Bone: A Multimodal Discourse Analysis of Pamungkas' Music Songs - Maria Klara Timorina Situmorang; T. Thyrhaya Zein (LingPoet: Journal of Linguistics and Literary Research, 2023)
Music is a form of communication used to convey emotions, ideas, and criticisms. It is the most significant cultural artifact of our time and the most pervasive artistic discipline in daily life. Individuals have a personal interest in music. It can bring joy to those who hear it. On the other hand, the music should relate to the visuals in the video clip, including color, sound, gesture, etc. This article analyzed and investigates the interpersonal significance of TO THE BONE. This descriptive-analytical study examined how various semiotics and modes, such as music, sound, speech, color, action, and facial expression, work together to create interpersonal meaning. The song is successful in capturing the attention of audiences around the world. The Singer is Indonesian. The majority of the song's lyrics are in English. The musical instrument and vocals are simple, but they can capture the attention of an international audience.